Integrating Strength and Technical Training in Women’s Rugby The Association Between Arm Muscle Strength and Passing Accuracy - Imron Nugroho Saputro; Nur Subekti; Septi Hariansyah; Mat Wajib; Amanda Eka Rismawati (Jurnal MensSana, 2026)
This study aims to analyze the relationship between arm muscle strength and passing accuracy in the Kebumen women's rugby team. The background of this study is the importance of upper-body muscle strength as a physiological component that supports basic technical skills in rugby. Practical passing skills require a combination of upper body strength, coordination, and stability to produce precise ball direction and speed. The research used a quantitative, correlational design. The sample consisted of twelve female athletes who actively participated in training and competitions. Data were collected through arm muscle strength tests and passing accuracy tests designed according to rugby game standards. Data analysis included validity, reliability, and correlation tests to assess relationships among variables. The results showed a significant positive relationship between arm muscle strength and passing accuracy, indicating that increased arm muscle strength directly contributes to the effectiveness of basic techniques in the game. This study confirms that upper-body muscle-strengthening training programs should be integrated with passing technique training to optimize coaching outcomes. These findings provide practical implications for coaches in designing evidence-based training programs and expand theoretical understanding of the relationship between physiological factors and technical performance in Indonesian women's rugby. Kata Kunci: accuracy, passing, rugby